1988
DOI: 10.1007/bf00394491
|View full text |Cite
|
Sign up to set email alerts
|

Rapid elicitation of second messengers by nanomolar doses of triacontanol and octacosanol

Abstract: Triacontanol (TRIA) increases the dry weight and alters the metabolism of rice (Oryza sativa L.) seedlings within 10 min of application to either the shoots or roots. This activity is prevented if octacosanol (OCTA, C28 primary alcohol) is applied with the TRIA on the roots or shoots. Triacontanol activity is also stopped if the OCTA is applied at least 1 min before the TRIA on the opposite part of the seedling.Triacontanol rapidly elicits a second messenger that moves rapidly throughout the plant resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 23 publications
0
32
2
Order By: Relevance
“…Ries and Houtz (1983) suggested that the hormonal effects of TRIA might be due to TRIA-induced alterations at the membrane level. TRIA-mediated activation of a number of membrane bound enzymes supports this assumption (Ries and Wert 1988;Ries 1991;Savithiry et al 1992). As per Ries et al (1990), TRIA treatment causes rapid elicitation of a specific second messenger, 9-b-L(') adenosine, which could induce extremely rapid physiological responses.…”
Section: Physiological and Biochemical Attributesmentioning
confidence: 72%
See 1 more Smart Citation
“…Ries and Houtz (1983) suggested that the hormonal effects of TRIA might be due to TRIA-induced alterations at the membrane level. TRIA-mediated activation of a number of membrane bound enzymes supports this assumption (Ries and Wert 1988;Ries 1991;Savithiry et al 1992). As per Ries et al (1990), TRIA treatment causes rapid elicitation of a specific second messenger, 9-b-L(') adenosine, which could induce extremely rapid physiological responses.…”
Section: Physiological and Biochemical Attributesmentioning
confidence: 72%
“…TRIA increased the dry weight as well as content of free amino acids, reducing sugars, and soluble protein of rice (Oryza sativa L.) and maize (Zea mays L.) plants within 5 min (Ries 1991). TRIA also elicited the appearance of L(')-adenosine in the roots of plants whose shoots were sprayed with its nanomolar concentrations within 1 min (Ries and Wert 1988). This was the first evidence that L(')-adenosine occurred in nature.…”
mentioning
confidence: 73%
“…
Since the discovery of the plant growth-regulating properties of TRIA, a primary alcohol that is a natural constituent of plant waxes, and its second messenger L(+)-adenosine, the rapid response kinetics to these compounds have been enigmatic (Ries and Wert, 1988;Ries, 1991).TRIA increased the dry weight, free amino acids, reducing sugars, and soluble protein of rice (Oryza sativa L.) and maize (Zea mays L.) plants within 5 min (Ries, 1991). TRIA also elicited the appearance of L(+)-adenosine in the roots of plants whose shoots were sprayed with nanomolar concentrations within 1 min (Ries and Wert, 1988).
…”
mentioning
confidence: 99%
“…TRIA applied to oat (Avena sativa L.) or tomato (Lycopersicon esculentum Mill.) shoots connected to rice roots by a 4-mm water column also resulted in the appearance of L(+)-adenosine (TRIM) in rice roots (Ries and Wert, 1988).In an attempt to determine other physiological responses to TRIA in addition to the elicitation of L(+)-adenosine, 20-to 25-d-old tomato seedlings were sprayed with water or TRIA, and after 1 min the plants were excised. Analysis of the diffusate from the excised shoots, as determined by HPLC and atomic absorption spectrophotometry, indicated large concentration differences in organic compounds and inorganic cations (unpublished data).…”
mentioning
confidence: 99%
See 1 more Smart Citation